Penguatan Nilai-Nilai Keislaman Melalui Kegiatan Pentas Seni Islami di MTs Mardiyah Islamiyah Kecamatan Panyabungan - Linur, Rahmat; Mulyadi, Rahmat; Fitri, Liwa Gusriza; Lubis, Pita Anggina; Batubara, Nurhanisah; Adilah, Nur; Haliza, Widiya; Sakinah; Lbs, Lusi Luria Mahdarini; Nasution, Salwa Hasyim (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to describe the implementation of Islamic arts performances and to analyse the reinforcement of Islamic values instilled through these activities at MTs Mardiyah Islamiyah in Panyabungan District. The study employs a qualitative approach using a descriptive method. Data were collected through interviews, observations, and documentation involving the head of the madrasah, Islamic Religious Education teachers, activity coordinators, and students. Data analysis was conducted using qualitative descriptive methods through the stages of data reduction, data presentation, and drawing conclusions, with data validity reinforced through triangulation of sources and techniques. The research findings indicate that Islamic arts performances are conducted systematically through the stages of planning, preparation, implementation, and evaluation, with the activities comprising nasyid, hadrah, Islamic drama, religious poetry, and calligraphy. These activities are capable of instilling Islamic values such as faith, worship, and morals, as well as supporting character traits such as discipline, responsibility, cooperation, and Islamic brotherhood. This study concludes that Islamic arts performances are an effective medium for fostering Islamic values and shaping the religious character of students within the madrasah environment.